The Role Of Community Mentoring In The Implementation Of Guidance To Corruption Criminal Clients Who Are Undergoing The Conditional Release Program : Study At Medan Class I Correctional Center - Lindawati Br Surbakti; Yasmirah Mandasari Saragih; Muhammad Azhali Siregar; Efraim Abigail Bukit (International Journal of Social Welfare and Family Law, 2024)
The crime of corruption is one part of a special crime in addition to having certain specifications that are different from general crimes. White Collar Crime is a term applied to people who wear ties who have high intelligence and commit criminal acts of corruption. As we all know, corruption is an extraordinary crime. Not only because it costs the state money, but it has an impact on all development programs, the low quality and quality of education, the low quality of facilities, equipment and infrastructure, as well as the problem of poverty that has not been addressed. Corruptors have taken away people's rights, human rights, and are against humanity. The principles of democracy which uphold transparency, accountability and integrity, as well as the security and stability of the Indonesian nation are threatened due to corruption crimes. Many corruptors who have been found guilty by the court and undergoing training in correctional institutions can quickly return to society because they have obtained their rights as correctional inmates, one of which is obtaining the conditional release program. The role of the Medan Class I Correctional Center is needed to realize the effectiveness of mentoring clients for criminal acts of corruption who are undergoing conditional release so that they can be accepted in society. Guidance provided to clients who have committed criminal acts of corruption must be carried out under supervision to determine the effectiveness of each guidance program provided until the guidance is finally terminated.